1996
DOI: 10.1515/bchm3.1996.377.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Choline Dehydrogenase Activity along the Rat Nephron

Abstract: A radioenzymatic microassay was developed to quantitate choline dehydrogenase activity in single microdissected nephron segments. This enzyme is the rate limiting step in the biosynthesis of betaine, which serves as an intracellular osmoregulatory organic solute in mammalian kidney. The enzyme localized in renal mitochondrial inner membrane forms betaine aldehyde, which in the assay is converted to betaine by oxidative treatment. A histochemical procedure based on the formazan detection of tetranitroblue tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…19 For example, studies in cellular and animal systems have shown that citrulline and choline metabolism occur primarily in proximal tubular cells. [20][21][22] Kynurenic acid, as would be expected for protein-bound solutes, has been identified as a substrate for organic anion transporters (hOAT1 and hOAT3) expressed on proximal tubular cells. 23,24 Thus, elevations in plasma citrulline, choline, and kynurenic acid may signal underlying tubulointerstitial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…19 For example, studies in cellular and animal systems have shown that citrulline and choline metabolism occur primarily in proximal tubular cells. [20][21][22] Kynurenic acid, as would be expected for protein-bound solutes, has been identified as a substrate for organic anion transporters (hOAT1 and hOAT3) expressed on proximal tubular cells. 23,24 Thus, elevations in plasma citrulline, choline, and kynurenic acid may signal underlying tubulointerstitial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The normal serum betaine concentration is 20 -144 M, however, in renal medullary cells, it may be concentrated up to 50 mM [84]. However, in renal medullary cells the betaine uptake from the extracellular space by BGT-1 is the most important mechanism [86]. However, in renal medullary cells the betaine uptake from the extracellular space by BGT-1 is the most important mechanism [86].…”
Section: Genes Involved In Osmolyte Accumulationmentioning
confidence: 99%
“…It is well established that betaine functions as an organic osmolyte not only in plants and bacteria but also in the renal medulla, where it helps medullary cells to survive the high osmolality of the medullary environment during antidiuresis (2,9); even bacteria growing in urine are protected against hypertonicity by taking up urinary betaine (6). In the kidney, betaine is synthesized from choline by choline dehydrogenase and betaine-aldehyde dehydrogenase in renal cortical cells (14,17,26). The highest betaine concentrations, however, are found in the renal medulla (3,30).…”
mentioning
confidence: 99%